ANGKA KEJADIAN UNPLANNED PREGNANCY PADA WANITA USIA PRODUKTIF DI KECAMATAN CANGKRINGAN PASCA ERUPSI MERAPI 2010 - , ADISTYA AYU KUSUMANINGTYAS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Method of contraception is a vital thing needed by couples of productive age because if interrupted access to contraceptive methods, will cause the occurrence of unplanned pregnancy. Access to contraceptive methodes is influenced by several things, one of which is the source of service, where the source of this service may be interrupted by reason of a disaster in the area. Purpose: To determine the prevalence of unplanned pregnancy in women of productive age in 2010 after the eruption of Merapi in Pagerjurang Kepuharjo resident Cangkringan Yogyakarta. Methods: This study used a retrospective study design. The research sample is needed as much as 86 people and then the data was collection on 06-20 March 2014. Data will be analyzed using univariate and bivariate. Univariate analysis used is distribusu frequency, while the bivariate analysis using Chi-square test and multiple logistic regression to determine the relationship of the independent variables and the dependent variable. Result: The prevalence of unplanned pregnancy women of productive age on Merapi Eruption in 2010 in the Pagerjurang was 27,3% (9/33). The incidence has increased when the people living in shelter that is 88,9% as well as the significant relationship between the difficulty of access to contraceptive methods the incidence of unplanned pregnancy. Conclusion: The prevalence of unplanned pregnancy after Merapi Eruption in 2010 was 27,3%. In a row, distribution of unplanned pregnancy in Pagerjurang resident from 2010 until 2014 are 0%, 66,7%, 0%, 22,2% and 11,1% and the highest incidence when the people living in shelters. The contraceptive methods that have significantly chenged after Merapi Eruption in 2010 was injectable contraception and a wife who did not use a contraceptive method.